Sally Ride : a photo biography of America's pioneering woman in space - O'Shaughnessy, Tam E. (Roaring Brook Press, 2015)
"A biography of the famous astronaut drawing on personal and family photographs from her childhood, school days, college, life in the astronaut corps, and afterward."--